Performance Evaluation Of Aac Blocks Incorporating Gsa And Foundry Waste As Partial Replacements (International Journal of Environmental Sciences, 2025)
The performance parameters of Autoclaved Aerated Concrete (AAC) blocks that partially substituted fine aggregates and cement with ground granulated sugarcane ash (GSA) and foundry trash, respectively, were assessed in this study. Five different mix designs with replacement amounts ranging from 0% to 25% were used in the experimental inquiry. Important characteristics were evaluated, including durability, porosity, thermal conductivity, water absorption, compressive strength, and dry density. According to the results, adding GSA and foundry waste decreased density and compressive strength while increasing porosity, which improved thermal insulating qualities. The 15% replacement mix (M2) performed best among the adjusted mixes, preserving structural integrity and increasing thermal efficiency. The results showed the potential of using industrial by-products in the production of AAC blocks, supporting efficient waste reutilization and sustainable building methods.